(untitled) (Journal of Libya for geographical studies, 2025)
Morocco, like other North African countries, is experiencing the effects of climate change, with its region being one of the most susceptible to drought and extreme hydrological events such as severe floods and droughts. This has led to water resource scarcity, ecosystem degradation, and a shift of populations from rural areas to urban centers. The recurring droughts over recent decades have resulted in the depletion of many water springs, particularly in arid and semi-arid regions. Given its geographical location, Morocco is among the countries most vulnerable to declining water resources. In the Upper Oum Er-Rbia Basin, which is the focus of this study, groundwater is a crucial component of the region’s water heritage, serving as a "water reservoir" for Morocco. This study aims to analyze the hydrological behavior of Ain Ikhorba from November 2023 to May 2024. This will be achieved through daily monitoring of the water level in the spring, conducting multiple measurements of water flow, and creating a calibration curve to understand the nature and functioning of this water source.